Frontonasal dysplasia- a rare case report - Sharma, Reena; Dogra, Poojan; Malhotra, Kapil; Kaushal, Vivek (International Journal of Research in Medical Sciences, 2017)
Frontonasal dysplasia (FND) is a rare malformative complex affecting the frontal portion of the face, the eyes and the nose; it may occur singly or associated with other clinical signs. We report here a rare case of a full-term male baby who presented with features of FND. There was no history of consanguinity, no positive family history. Antenatal ultrasonography was normal. Though this baby did not survive because the defects were not compatible for the survival. But the developing nations still have handicap in the management of such cases in term of fiancés, surgical correction of such major defects, education and social support in these patients.